Evaluating Interactive Information Retrieval Systems: Opportunities and Challenges - Belkin, Nicholas; Dumais, Susan; Scholtz, Jean; Wilkinson, Ross (Proceedings of CHI 2004, 2004)
Information retrieval or search plays an important role in a wide range of information management and electronic commerce tasks. In spite of the importance of information retrieval, search systems are often poorly designed from a human computer interaction perspective. The goal of this SIG is to articulate some of the opportunities and challenges in designing and evaluating highly interactive information retrieval systems.